Enhancing Speaking Abilities Through Applied Behavior Analysis: A Teacher-Led Intervention for 5-6 Year-Old Children with Speech Delays in Inclusive Kindergarten Settings - Metasari, Dian; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Speech delay affects 5-10% of preschool children globally, significantly impacting their communication abilities, social interaction, and academic readiness. Applied Behavior Analysis (ABA) has emerged as a promising intervention approach, yet limited research exists on teacher-implemented ABA methods for speech-delayed children in inclusive educational settings. This study investigated the effectiveness of ABA methods in improving speaking abilities among children with speech delays aged 5-6 years in an inclusive kindergarten environment. A classroom action research design was employed at TK Negeri 1 Rantau Pulung, involving five purposively selected children with identified speech delays. The intervention was implemented across three progressive cycles using systematic ABA techniques including instruction-response-reinforcement sequences, visual aids, environmental exploration, and role-playing activities. Data were collected through structured observations, speaking ability assessments, interviews, and documentation. Assessment criteria included vocabulary production, sentence construction, pronunciation accuracy, and social engagement, rated on a four-point developmental scale. Significant improvements were observed across all intervention cycles. Pre-intervention assessment showed 80% of children in the "Not Yet Developing" category, with no children demonstrating age-appropriate abilities. By Cycle III, 60% achieved "Developing Very Well" status, 20% reached "Developing as Expected," and 20% maintained "Beginning to Develop." The most substantial progress occurred between Cycles I and II, with continued enhancement in Cycle III. Teacher-implemented ABA methods effectively improve speaking abilities in children with speech delays. The systematic intervention approach provides a replicable framework for inclusive education settings, demonstrating that classroom teachers can successfully deliver evidence-based interventions without specialized therapeutic training.